Genome-Wide Association Study Detects Loci Involved in Scab Susceptibility in Japanese Apricot - Koji Numaguchi; Tomoaki Kashiwamoto; Ryo Ishikawa; Takashige Ishii; Yuto Kitamura (Horticulturae, 2023)
Japanese apricot (Prunus mume) is an important fruit tree in East Asia. ‘Nanko’, the primary cultivar of Japanese apricots, usually suffers from scab, a disease caused by Venturia carpophila. However, there have been few reports on the phenotypic variation in scab resistance/susceptibility and the underlying genetic factors. In this study, we investigated the severity of naturally occurring scabs based on fruit lesions in 108 Japanese apricot accessions over four consecutive years. In each year, both resistant and susceptible accessions were observed, and significant annual correlations were detected among the ratios of diseased fruits (Rt; 0.52–0.76) and among the disease severity indices (Sv; 0.55–0.79). We also conducted a genome-wide association study (GWAS) based on exon-targeted resequencing, and significant peaks were detected in the data from 2017 and 2018. The candidate genes involved in disease resistance are located near nine single-nucleotide polymorphisms. These genes may be associated with the susceptibility of ‘Nanko’ lineages to scab. These findings shed light on the phenotypic and genetic profiles of scab resistance in P. mume and will assist future breeding programs with improving scab resistance.